2017
DOI: 10.1016/j.intmar.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

To Share and Protect: Using Regulatory Focus Theory to Examine the Privacy Paradox of Consumers’ Social Media Engagement and Online Privacy Protection Behaviors

Abstract: Consumers’ personal information often informs retailers’ marketing efforts in terms of creating value in the online marketplace. This study examines four factors related to consumers’ social media engagement and online privacy protection behaviors. Regulatory focus, social exchange, and marketing relationship theories explain the online consumer personal information share-and-protect model developed. Consumers aged 18–64 years across the United States participated in this survey research. The results suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 52 publications
8
83
0
2
Order By: Relevance
“…Literature confirms these findings: when a brand is seen as trustworthy, customers tend to trust their personal information to the brand, increasing the chances of a long-term relationship (Berry, 1995;Rambalducci, Borinelli, & Oliveira, 2012). Our results also reinforce the finding from Mosteller and Poddar (2017) and Huang and Chen (2018). The first study confirmed the positive influence of trust in user engagement in social networks, a fundamental aspect in customer relationship developing.…”
Section: Resultssupporting
confidence: 90%
“…Literature confirms these findings: when a brand is seen as trustworthy, customers tend to trust their personal information to the brand, increasing the chances of a long-term relationship (Berry, 1995;Rambalducci, Borinelli, & Oliveira, 2012). Our results also reinforce the finding from Mosteller and Poddar (2017) and Huang and Chen (2018). The first study confirmed the positive influence of trust in user engagement in social networks, a fundamental aspect in customer relationship developing.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, privacy concerns were also found to have a negative impact on self-disclosure behavior on social networking sites. These findings concur with previous studies [21,57,83,84,85] that demonstrate that user behavior on online social networks is dependent on their perceptions and experience with privacy. SNS users generally expect that that the SNS service provider protects that private data and so when their privacy is abused they are inclined to think that the site did not meet its responsibilities.…”
Section: Discussionsupporting
confidence: 92%
“…Other researchers could consider obtaining data from stronger economic environments and emerging markets and investigating its moderating effect on self-disclosure on SNS. In further studies, other researchers could explore the interrelationship between the factors identified in the current study, for instance the effect the privacy invasion experience could have on privacy concerns [84]. Finally, other researcher could explore the moderating role of gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…The internal controller of COSO 1992 and SAS 78 is a process influenced by the board of commissioners, management and other business unit personnel designed to gain reasonable assurance about the achievement of objectives in the following matters: (1) Reliability of financial reporting (2) Compliance with applicable laws and regulations (3) Effectiveness and efficiency of operation (Daniela & Attila, 2013;Rae et al, 2017). The internal control component of COSO (Committee of Sponsoring Organization) consists of five components: control environment, risk assessment, control activities, information and communication, monitoring (Mosteller & Poddar, 2017) Researches on the implementation of COSO-based internal control and good university governance refer to studies by Sawalqa & Qtish (2012), Agyei-Mensah (2016), Ghozali & Achmad (2017), and Ansori (2018). Sawalqa & Qtish's (2012) research aims to examine the role of internal control elements: control environment, risk assessment, control activities, information and communication, and monitoring, in improving the pillars of corporate governance: accountability, fairness, responsibility answer, and transparency in the insurance company.…”
Section: Introductionmentioning
confidence: 99%